Blended teaching and learning: Exploring the concept, barriers to implementation and designing of learning resources - Janse van Rensburg, E. D.; Oguttu, J. W. (South African Journal of Higher Education, 2022)
With the advent of the coronavirus disease 2019 (COVID-19), several institutions worldwide have adopted the blended mode of teaching and learning. However, literature on this concept in South Africa and on the African continent is scarce. This scoping review explores the concept of blended approach to training and how to design resources for the blended teaching and learning approach. In addition, the review investigates barriers to the implementation of blended learning. The findings of this study demonstrate that the understanding of the concept of blended teaching and learning is not homogenous and is often left to individual academics to decide on the approach. The review identified several hurdles that need to be addressed for successful implementation of blended teaching and learning, however these are not specific to South African institutions. Available literature on studies done elsewhere and in South African, suggest that some of the identified barriers to adoption of blended teaching and learning are real, while others are perceived or imagined. Lastly, the authors observed that there are several approaches to designing learning resources for the blended mode of teaching and learning. The choice of approach is dependent on the intended purpose for which the specific design is adopted. There is a need for studies that specifically investigate blended learning in Universities in South Africa and on the continent to help identify barriers to adopting blended teaching and learning among institutions that are specific to the South African and African context. Institutions adopting the blended teaching and learning mode of delivery, need to be unambiguous in their philosophy of blending teaching and learning and not leave it to the implementing academics. Policymakers can use the information generated in this review to recommend minimum requirements for a blended delivery mode in public institutions of higher learning.